2018
DOI: 10.1039/c8ra02694g
|View full text |Cite
|
Sign up to set email alerts
|

Proton conductivity resulting from different triazole-based ligands in two new bifunctional decavanadates

Abstract: To investigate the effects of triazole-based ligands in polyoxovanadates (POVs) on proton conductivity, we designed and synthesized two decavanadate-based POVs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 45 publications
0
12
0
Order By: Relevance
“…The influence of temperature on the proton conductivity of compounds is primarily owing to that the mobility of H 2 O molecules acting as proton carriers increases with the temperature increase . It should be noted that the proton conductivity of compound 1 , 1.94×10 −2 S cm −1 at 85 °C and 95 % RH, is obviously higher than those of mostly reported proton‐conducting materials based on molybdenum oxides, and comparable to those of mostly excellent proton‐conduction materials . In Table S1, the comparison of proton conductivities of 1 and 2 with those of other molybdenum oxides and crystalline proton conductor materials are given.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The influence of temperature on the proton conductivity of compounds is primarily owing to that the mobility of H 2 O molecules acting as proton carriers increases with the temperature increase . It should be noted that the proton conductivity of compound 1 , 1.94×10 −2 S cm −1 at 85 °C and 95 % RH, is obviously higher than those of mostly reported proton‐conducting materials based on molybdenum oxides, and comparable to those of mostly excellent proton‐conduction materials . In Table S1, the comparison of proton conductivities of 1 and 2 with those of other molybdenum oxides and crystalline proton conductor materials are given.…”
Section: Resultsmentioning
confidence: 99%
“…[25] It should be noted that the proton conductivity of compound 1, 1.94 × 10 À 2 S cm À 1 at 85°C and 95 % RH, is obviously higher than those of mostly reported proton-conducting materials based on molybdenum oxides, [26] and comparable to those of mostly excellent proton-conduction materials. [27][28][29][30][31][32] In Table S1, the comparison of proton conductivities of 1 and 2 with those of other molybdenum oxides and crystalline proton conductor materials are given.…”
Section: Proton Conductivity Of 1 Andmentioning
confidence: 99%
“…30 Developing a new high-efficiency proton conductor with an environment-friendly and simple method is a challenging topic, which is of great significance for quantification in the future. 31,32 Proton-conducting materials with hydrophilic groups on the surface, such as hydroxyl ( OH) and carboxyl groups ( COOH), can form a continuous and order conducting path along the interface, which can promote faster proton conduction. [33][34][35] In 2011, Jung reported that graphene oxide (GO)-Nafion composites showed high proton conductivity of 0.0396 and 0.119 S cm À1 even with only 0.1% and 1% GO content, and the physical stability of the hybrid membrane was significantly improved.…”
Section: Introductionmentioning
confidence: 99%
“…What’s more, because of the potential applications of POMs in optical, catalytic, electrical, and magnetic properties, an increasing number of researchers pay attention to the synthesis of bifunctional POM-based materials in recent years. As one of the most important parts of the catalytic properties, photocatalytic properties were investigated for the reported molybdophosphate hybrids, , from which it was disputable that the unique redox property and excellent photocatalytic activity made the P 4 Mo 6 cluster a potential promising photocatalyst for the CO 2 photoreduction.…”
Section: Introductionmentioning
confidence: 99%